Macrophage deficiency of miR‐21 promotes apoptosis, plaque necrosis, and vascular inflammation during atherogenesis. Issue 9 (3rd July 2017) - Canfrán‐Duque, Alberto; Rotllan, Noemi; Zhang, Xinbo; Fernández‐Fuertes, Marta; Ramírez‐Hidalgo, Cristina; Araldi, Elisa; Daimiel, Lidia; Busto, Rebeca; Fernández‐Hernando, Carlos; Suárez, Yajaira
Abstract: Atherosclerosis, the major cause of cardiovascular disease, is a chronic inflammatory disease characterized by the accumulation of lipids and inflammatory cells in the artery wall. Aberrant expression of microRNAs has been implicated in the pathophysiological processes underlying the progression of atherosclerosis. Here, we define the contribution of miR‐21 in hematopoietic cells during atherogenesis. Interestingly, we found that miR‐21 is the most abundant miRNA in macrophages and its absence results in accelerated atherosclerosis, plaque necrosis, and vascular inflammation. miR‐21 expression influences foam cell formation, sensitivity to ER‐stress‐induced apoptosis, and phagocytic clearance capacity. Mechanistically, we discovered that the absence of miR‐21 in macrophages increases the expression of the miR‐21 target gene, MKK3, promoting the induction of p38‐CHOP and JNK signaling. Both pathways enhance macrophage apoptosis and promote the post‐translational degradation of ABCG1, a transporter that regulates cholesterol efflux in macrophages. Altogether, these findings reveal a major role for hematopoietic miR‐21 in atherogenesis. Synopsis: The present work defines the major contribution of miR‐21 in regulating macrophage inflammation, apoptosis, efferocytosis and lipid metabolism during atherogenesis. miR‐21 is the most abundant miRNA in macrophages. Lack of miR‐21 in the hematopoietic system accelerates atherogenesis and promotes adverse plaque remodeling. In the absence of miR‐21, macrophages exhibit a pro‐inflammatory phenotype, and their phagocytic activity is reduced. Deficiency of miR‐21 in macrophages induces ER‐stress‐mediated apoptosis and promotes activation of MKK3/p38 and JNK signaling pathways. Lack of miR‐21 in macrophages promotes the degradation of ABCG1, impairing the efflux of cholesterol and increasing the foam cell formation. Abstract : The present work defines the major contribution of miR‐21 in regulating macrophage inflammation, apoptosis, efferocytosis and lipid metabolism during atherogenesis.